2010
DOI: 10.1681/asn.2008111133
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p53 Promotes Renal Injury in Acute Aristolochic Acid Nephropathy

Abstract: Ingestion of aristolochic acid (AA) can cause AA nephropathy (AAN), in which excessive death of tubular epithelial cells (TECs) characterize the acute phase. AA forms adducts with DNA, which may lead to TEC apoptosis via p53-mediated signaling. We tested this hypothesis both by studying p53-deficient mice and by blocking p53 in TECs with its inhibitor pifithrin-␣. AA induced acute AAN in wild-type mice, resulting in massive apoptotic and necrotic TEC death and acute renal failure; p53 deficiency or pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
100
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 38 publications
7
100
2
Order By: Relevance
“…12,17 The involvement of p53 has been reported in nephrotoxic injury and IRI. [18][19][20] Although previous studies showed that p53 levels are significantly increased in the medulla after IRI, 9 the contribution of p53 to tubular cell death and kidney dysfunction is still unclear. 8,9,[20][21][22] Thus, considering the importance of p53 in promoting apoptotic/necrotic cell death, we hypothesized that knockout (KO) of p53 in the proximal tubule significantly reduces tubular cell death and kidney dysfunction after IRI.…”
mentioning
confidence: 99%
“…12,17 The involvement of p53 has been reported in nephrotoxic injury and IRI. [18][19][20] Although previous studies showed that p53 levels are significantly increased in the medulla after IRI, 9 the contribution of p53 to tubular cell death and kidney dysfunction is still unclear. 8,9,[20][21][22] Thus, considering the importance of p53 in promoting apoptotic/necrotic cell death, we hypothesized that knockout (KO) of p53 in the proximal tubule significantly reduces tubular cell death and kidney dysfunction after IRI.…”
mentioning
confidence: 99%
“…[13][14][15][16] p53 was also implicated in kidney injury induced by folic acid, aristolochic acid, and glycerol injection. [17][18][19] As a result, inhibition of p53 may offer an effective therapy for AKI, 12,16,20 and small interfering RNA (siRNA) targeting p53 has been tested for AKI in clinical trials (http://clinicaltrials.gov/ct2/results? term=I5NP&Search=Search).…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] This transcription factor primarily responds to cellular stress and DNA damage by halting the cell cycle and by promoting apoptosis in extreme cases of cell stress. 12,13 Whereas the primary role of p53 activation is to safeguard the genome and prevent malignant transformation, its role in AKI is less straightforward and can be detrimental inasmuch as it can trigger cell death in sublethally injured tubular cells.…”
mentioning
confidence: 99%